MDMX: a novel p53-binding protein with some functional properties of MDM2. - Shvarts, A (1996)
Here we report the isolation of a cDNA encoding a new p53-associating protein. This new protein has been called MDMX on the basis of its structural similarity to MDM2, which is especially notable in the p53-binding domain. In addition, the putative metal binding domains in the C-terminal part of MDM2 are completely conserved in MDMX. The middle part of the MDMX and MDM2 proteins shows a low degree of conservation. We can show by co-immunoprecipitation that the MDMX protein interacts specifically with p53 in vivo. This interaction probably occurs with the N-terminal part of p53, because the activity of the transcription activation domain of p53 was inhibited by co-transfection of MDMX. Northern blotting showed that MDMX, like MDM2, is expressed in all tissues tested, and that several mRNAs for MDMX can be detected. Interestingly, the level of MDMX mRNA is unchanged after UV irradiation, in contrast to MDM2 transcription. This observation suggests that MDMX may be a differently regulated modifier of p53 activity in comparison with MDM2. Our study indicates that at least one additional member of the MDM protein family exists which can modulate p53 function.